Menstrual health of in-school adolescents in Ibadan: knowledge, attitudes and consequences (2009)
We evaluated the knowledge, attitudes to and consequences of menstrual morbidities among in –school adolescents in Ibadan and determined their effect on school attendance. The pattern of drug use for menstrual symptoms was also assessed. Self-administered questionnaires were given to 1194 respondents in secondary schools chosen by randomization. The mean age of respondents was 15.7+ years while 86.1% were aged between 10-17 years. The most prevalent menstrual disorder was dysmenorrhea (87.3%). The commonest source of information about the menstrual cycle was from mothers (71%) while 0.5% of adolescents obtained information from health care givers. Menstrual symptoms were treated with non-pharmacological means in 53.1%. Of girls using pharmacologic agents 44% of them obtaining over the counter medications (OTC). Forty four percent of respondents missed school for 6-7 weeks per session following dysmenorrhea while 19% of them required hospital admission. It was concluded that there is insufficient knowledge of the menstrual cycle and its abnormalities among adolescents. Menstrual health should be introduced as part of reproductive health programs in school curricula in Nigeria.